Echocardiographic predictors of ventricular arrhythmias in patients with left ventricular assist devices and implantable cardioverter-defibrillator - Efimova, Elena; Zeynalova, Samira; Eifert, Sandra; Dashkevich, Alexey; Borger, Michael Andrew; Meyer, Anna L.; Garbade, Jens; Darma, Angeliki; Bode, Kerstin; Arya, Arash (Journal of cardiovascular electrophysiology, 2025)
Aim: To evaluate the predictive value of preoperative echocardiographic parameters for occurrence of VAs in patients with preexisting ICD undergoing LVAD implantation. Methods and Results: All consecutive patients (n = 264) with previous ICD who underwent LVAD surgery between May 2011 and December 2019 at our institution were included. The patients were predominantly male (89%) with NICM (59%) and a mean age of 59 ± 10 years. All LVADs were continuous flow device (154 HVAD, 21 HeartMate II, and 89 HeartMate 3). A total of 102 (39%) patients had VAs in the first year after LVAD implantation. We compared echocardiographic parameters in patients with and without VAs before LVAD, at 1 month and 1 year after LVAD implantation. Increased pre-LVEDD ≥ 72 mm predicted the occurrence of VAs after LVAD implantation for ICM patients (HR: 2.9, 95% confidence interval (CI): [1.3-6.6], p = 0.012), while a larger pre-RVEDD ≥ 46 mm was predictive in NICM patients (HR: 2.8, (CI): [1.4-5.9], p = 0.004). Moreover, a larger RVEDD at 1 year after LVAD was highly associated with VAs in the first year after LVAD implantation (50 ± 10 vs. 45 ± 8 mm, p = 0.001). All patients demonstrated a significant decrease in LVEDD as well as a reduction in severity of mitral and tricuspid regurgitation during 1 year after LVAD implantation, reflecting left ventricular unloading through the LVAD. Conclusions: Larger left and right ventricular diameters before LVAD predict the occurrence of VAs after LVAD implantation in ICM and NICM patients. Persistent RV remodeling post-LVAD is also associated with VAs.
Zuerst veröffentlicht: 16. Dezember 2024